Taking Custody, Giving Access: A Postcustodial Role for a New Century - Bastian, Jeannette A. (Archivaria, 2002)
This article considers the relationship between custody and access focusing on the vital role that access to historical records plays in the construction of community memory. It explores the principle of archival custody as it has developed primarily in the English-speaking world, its historical background, its mid-twentieth century evolution into postcustodialism, and suggests that access be a primary role for the custodian in the new century.